Ketidakadilan perjanjian kewangan IMF: kesan ke atas negara-negara anggota OIC - Salawati Mat Basir, (Fakulti Undang - Undang, 2009)
For almost all of the OIC member states, being either low or middle-income economies, financial problem is a serious obstacle to their development efforts and economic growth. As a solution, they seek the financial assistance from the International Monetary Fund (IMF).The IMF, in cooperation with the World Bank, provide financial assistance to them, but apply a neoliberal economic ideology as a precondition to receiving the assistance. This article attempts to show the negative impacts of these preconditions on the OIC member countries. Secondly, it presents a discussion of the IMF’s debt relief program and its implications on the OIC member countries, particularly for the OIC-Heavily Indebted Poor Countries (HIPCs). Thirdly, it explores how the IMF has directed the OIC member countries to peg their currency on the US dollar and thereby open them widely to speculative activities. Finally, this article unveils how the unfairness of the IMF financial agreement affects the OIC member countries and the Muslims around the world and why the OIC must take drastic actions to overcome these situations